Conditional cell reprogramming involves non-canonical β-catenin activation and mTOR-mediated inactivation of Akt. - Frank A Suprynowicz (PLoS ONE, 2017)
The combination of irradiated fibroblast feeder cells and Rho kinase inhibitor, Y-267362, converts primary epithelial cells growing in vitro into an undifferentiated adult stem cell-like state that is characterized by long-term proliferation. This cell culture method also maintains the proliferation of adult epithelial stem cells from various tissues. Both primary and adult stem cells retain their tissue-specific differentiation potential upon removal of the culture conditions. Due to the ability to modulate the proliferation and differentiation of the cells, this method is referred to as conditional reprogramming and it is increasingly being used in studies of tumor heterogeneity, personalized medicine and regenerative medicine. However, little is known about the biology of these conditionally reprogrammed (CR) cells. Previously we showed that β-catenin activation, a hallmark of stem cells in vivo, occurs in CR human ectocervical cells (HECs). Here we show that β-catenin-dependent transcription is necessary for the induction of epithelial stem cell markers, and that β-catenin is activated via a non-canonical pathway that is independent of Wnt and Akt/GSK-3. Active Akt actually decreases due to increased mTOR signaling, with a consequent increase in dephosphorylated, active GSK-3. Despite the increase in active GSK-3, β-catenin associates with protein phosphatase 2A (PP2A) and is activated. Inhibition of PP2A catalytic activity reduces both the level of active β-catenin and the acute induction of stem cell markers, suggesting an important role for PP2A in the activation of β-catenin. Moreover, we demonstrate similar results using human prostate and breast cells, indicating that these changes are not restricted to ectocervical epithelial cells and may represent a more fundamental property of conditional reprogramming.